News Frames on Transfemicide: A Look at the Mexican Digital Press - Rojas Estrada, Elizabeth Guadalupe (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
From the framing approach, the media treatment of transfemicide carried out by the websites of four Mexican media has been analyzed: El Universal, La Jornada, Milenio Diario and Reforma. The detection and characterization of the news frames have been done inductively through the mixed method proposed by Amparo Moreno Sardà, which preserves the traditional quantitative perspective of content analysis and qualitative evaluations. This methodology leaves as remarkable findings the existence of a preferentially androcentric informative look that places trans women in a position of inferiority and the predominant use of frames that dehumanize the victims and relativize the continuum of violence they suffer.